An in silico approach for the identification of detrimental missense SNPs and their potential impacts on human CRY2 protein (Journal of Bangladesh Academy of Sciences, 2025)
Cryptochrome 2 (CRY2) is one of the four proteins of the cell-autonomous molecular  clock  in  mammals.  Non-synonymous  SNPs  of  the  cry2  gene, resulting  in  missense  variants  of  CRY2,  were  correlated  with  metabolic disorders, cancers, and autism spectrum disorders. This in silico analysis aimed to investigate these missense SNPs having deleterious structural and functional impacts on the human CRY2 protein. Multiple computational tools, homology modeling, and molecular dynamic simulation reported an impact on protein structural stability, function, and binding with PER2 and FBXL3. Our results suggest that missense variants of hCRY2 with L74P, L274P, L309P, F315V, and Y485H mutations were the most destabilizing. These were found to have an overall altered structure, especially in the FAD binding pocket, which in turn can impact the binding of CRY activating compounds, regulatory proteins FBXL3 and PER2. These five missense variants warrant detailed in vitro and in vivo investigations to solidify our findings.J. Bangladesh Acad. Sci. 49(1); 57-72: June 2025